Pengaruh Latihan Power play Terhadap Kontribusi Goalkeeper Dalam Permainan Futsal - Mauladani, Rahman Fajar; Hermawan, Irwan; Permadi, Asep Angga (Universitas Hamzanwadi, 2024)
SMAN 17 Garut has extracurricular futsal activities, but its achievements are still relatively low. This study aims to reveal the effect of the power play training program on the goalkeeper's role in futsal matches when competing. The method used in this research is quantitative, using an experimental approach with a pre-experiment design with one group pretest-post test. The population of this study included all futsal extracurricular students. This study uses non probability sampling with total sampling or saturated sampling techniques. The data collection technique in this study used a playing skills test or GPAI. The data analysis process uses the SPSS version 26 program, and includes normality test, homogeneity test, and hypothesis testing. The results have an average pretest of 0.3086 and posttest of 0.3986. From the results of the hypothesis test, the p-value obtained is 0.000 based on the test criteria that the value is smaller than 0.05 which indicates that there is a significant difference. The results of the discussion can be concluded that power play training on goalkeeper contributions during futsal games has a good or increasing impact.